EXPERIMENTAL STUDY OF ARSENIC SPECIATION IN VAPOR PHASE TO 500°C: IMPLICATIONS FOR AS TRANSPORT AND FRACTIONATION IN LOW-DENSITY CRUSTAL FLUIDS AND VOLCANIC GASES - Pokrovski G.S.; Roux J.; Zakirov I.V.; Testemale D.; Hazemann J.L.; Bychkov A.Y.; Golikova G.V. (My University, 2002)
The stoichiometry and stability of arsenic gaseous complexes were determined in the system As-H2O ± NaCl ± HCl ± H2S at temperatures up to 500°C and pressures up to 600 bar, from both measurements of As(III) and As(V) vapor–liquid and vapor–solid partitioning, and X-ray absorption fine structure (XAFS) spectroscopic study of As(III)-bearing aqueous fluids. Vapor–aqueous solution partitioning for As(III) was measured from 250 to 450°C at the saturated vapor pressure of the system (Psat) with a special titanium reactor that allows in situ sampling of the vapor phase. The values of partition coefficients for arsenious acid (H3AsO3) between an aqueous solution (pure H2O) and its saturated vapor (K = mAsvapor /mAsliquid) were found to be independent of As(III) solution concentrations (up to ∼1 to 2 mol As/kg) and equal to 0.012 ± 0.003, 0.063 ± 0.023, and 0.145 ± 0.020 at 250, 300, and 350°C, respectively. These results are interpreted by the formation, in the vapor phase, of As(OH)3(gas), similar to the aqueous As hydroxide complex dominant in the liquid phase. Arsenic chloride or sulfide gaseous complexes were found to be negligible in the presence of HCl or H2S (up to ∼0.5 mol/kg of vapor). XAFS spectroscopic measurements carried out on As(III)-H2O (±NaCl) solutions up to 500°C demonstrate that the As(OH)3 complex dominates As speciation both in dense H2O-NaCl fluids and low-density supercritical vapor. Vapor–liquid partition coefficients for As(III) measured in the H2O-NaCl system up to 450°C are consistent with the As speciation derived from these spectroscopic measurements and can be described by a simple relationship as a function of the vapor-to-liquid density ratio and temperature. Arsenic(III) partitioning between vapor and As-concentrated solutions (>2 mol As/kg) or As2O3 solid is consistent with the formation, in the vapor phase, of both As4O6 and As(OH)3. Arsenic(V) (arsenic acid, H3AsO4) vapor–liquid partitioning at 350°C for dilute aqueous solution was interpreted by the formation of AsO(OH)3 in the vapor phase.The results obtained were combined with the corresponding properties for the aqueous As(III) hydroxide species to generate As(OH)3(gas) thermodynamic parameters. Equilibrium calculations carried out by using these data indicate that As(OH)3(gas) is by far the most dominant As complex in both volcanic gases and boiling hydrothermal systems. This species is likely to be responsible for the preferential partition of arsenic into the vapor phase as observed in fluid inclusions from high-temperature (400 to 700°C) Au-Cu (-Sn, -W) magmatic-hydrothermal ore deposits. The results of this study imply that hydrolysis and hydration could be also important for other metals and metalloids in the H2O-vapor phase. These processes should be taken into account to accurately model element fractionation and chemical equilibria during magma degassing and fluid boiling.